Organisational and strategic communication research: european perspectives - Gonçalves, Gisela Marques Pereira (2014)
The diversity represented in this book, not only in respect to author nationality, but also in theoretical and empirical approaches, reflects one of the most salient features of the European Communication Research and Education Association: Organisational and Strategic Communication Section’s identity. The spectrum of themes analysed in this collection – crisis communication, government communication, organisational communication and social media, corporate social responsibility, health media relations – demonstrates the range and vitality of organisational and strategic communication research in Europe.